PHOTOJOURNALISM REDUCES CAREGIVER BURDEN AND DEPRESSION IN DEMENTIA CAREGIVERS. (11th November 2018) - Kovaleva, M; Wharton, W; Epps, F; Bridwell, L; Tate, R; Dorbin, C; Hepburn, K
Abstract: Most persons living with dementia rely on informal caregivers. This study aimed to describe a pilot photojournalism program for 10 caregivers of persons living with dementia with respect to caregivers' mood, depressive symptoms, and experience. A professional photographer taught photography in a four-session workshop. Caregivers photographed what they saw as representative of their experience and discussed the photographs in class. Quantitative exploration consisted of pre- and post-program comparison in caregiver burden (Zarit Burden Interview) and depression (Patient-Reported Outcomes Measurement Information System – Short Form – Depression). Qualitative exploration included investigators' observations, viewing photographs, and recording caregivers' comments on their photographs. For participants with pre- and post-program data (N=5), caregiver burden decreased significantly (p = 0.037) and depression decreased non-significantly (p = 0.066). Statistically non-significant but clinically meaningful reductions in caregiver burden and depression were attained. Analysis of photographs and caregivers' accompanying commentaries yielded three themes: caregivers' emotional well-being, shared experiences, and classroom engagement. Qualitative data demonstrated caregivers' satisfaction with the program and their ability to express their experiences in a new creative format and discuss their challenges, using photographs as daily life examples. These results demonstrated efficacy of this photojournalism intervention in the reduction of caregiver burden and depression. Caregivers could reflect upon their work with other participants and get their feedback. Future studies should employ a larger sample size and test more patient- and caregiver-centered variables. Provided their positive effect on dyads, these programs may be more widely adopted by healthcare, educational, and community agencies, such as museums.